PENERAPAN MODEL PEMBELAJARAN GUIDED DISCOVERY UNTUK MENINGKATKAN AKTIVITAS BELAJAR BIOLOGI SISWA KELAS X-2 SMA MUHAMMADIYAH 1 KARANGANYAR TAHUN PELAJARAN 2013/2014 - Utami, Fitri Astuti Wahyu; Sajidan, Sajidan; Dwiastuti, Sri (Universitas Sebelas Maret, 2015)
The purpose of the research was to improve student’s biology learning activity in class X-2 SMA Muhammadiyah 1 Karanganyar in the academic year 2013/2014 through by implementation of Guided Discovery learning model. The research was a classroom action research which performed in two cycles. Each cycle consisted of 4 phases, that was planning, action, observation, and reflection. Subject of the research was students of class X-2 SMA Muhammadiyah 1 Karanganyar in the academic year 2013/2014. Data of the research was obtained by test and non test technique consisted observation, interview and documentation. The obtained data were analyzed using descriptive technique and were validated using triangulation of methods. Target of the research was to achieve 75,00% for each aspect of student’s biology learning activity. The results of the research showed the percentage student’s biology learning activity aspect for oral activities pre cycle (31,94%), cycle I (69,50%), and cycle II (75,00%), motor activities pre cycle (25,46%), cycle I (77,00%), and cycle II (79,33%), mental activities pre cycle (31,02%), cycle I (72,26%), and cycle II (79,81%), emotional activities pre cycle (30,56%), cycle I (81,00%), and cycle II (87,38%), writing activities pre cycle (46,30%), cycle I (77,00%), and cycle II (80,77%), listening activities pre cycle (36,11%), cycle I (76,00%), and cycle II (82,41%), drawing activities pre cycle (27,78%), cycle I (63,00%), and cycle II (78,70%), and visual activities pre cycle (30,56%), cycle I (72,00%), and cycle II (78,70%). The results showed that the average percentage student’s biology learning activity aspect such as pre cycle (32,47%), cycle I (73,47%), and cycle II (80,26 %). The conclusion of the research is the implementation of Guided Discovery learning model can improve student’s biology learning activity in class X-2 SMA Muhammadiyah 1 Karanganyar in the academic year 2013/2014. Keywords : Guided Discovery, Student’s Biology Learning Activity